The Vertical Soft Tissue Thickness and Subcrestal Implant Placement as Factors for Peri-implant Crestal bone Stability - Veljanovski, Darko; Atanasovska-Stojanovska, Aneta; Pivkova Veljanovska, Aleksandra; Mijiritsky, Eitan; Bollen, Curd (Scientific Foundation SPIROSKI, 2021)
Aim The aim of this prospective study was to determine the influence of vertical soft tissue thickness on bone level changes in platform-switched implants placed eqicrestally or subcrestally and restored with screw-retained or cement-retained restorations. Methods Platform-switched bone-level implants were placed in a single stage manner in the posterior mandibular region. Implant sites were divided into thick (control) and thin (test) vertical soft tissue groups. The implants in the control group were placed equicrestally. The implant sites from the control group were randomly allocated to receive equicrestally or subcrestally placed implants. Bone remodeling/loss was radiographically measured at baseline, three months postoperatively and six months after delivery of final prosthetic restoration. Results The mean crestal bone loss values three months postoperatively and six months post prosthetic restoration were higher in sites with thin versus sites with thick gingiva. In implant sites with thin gingiva, subcrestally placed implants presented less bone loss than eqicrestally placed implants. Conclusion Platform switched implants are prone to more bone loss when they are placed in sites with thin soft tissue, regardless of the type of final restoration (screw-retained or cement-retained). Subcrestal placement of platform-switched implants can prevent crestal bone loss in sites with vertical soft tissue thickness < 3 mm.